Crime and Growth Convergence : Evidence from Mexico - Enamorado, Ted; López-Calva, Luis F.; Rodriguez Castelan, Carlos (World Bank, Washington, DC, 2014)
Scholars have often argued that crime deters growth, but the empirical literature assessing such effect is scarce. By exploiting cross-municipality income and crime data for Mexico -- a country that experienced a high increase in crime rates over the past decade -- this study circumvents two of the most common problems faced by researchers in this area. These are: (i) the lack of a homogenous, consistently comparable measure of crime and (ii) the small sample problem in the estimation. Combining income data from poverty maps, administrative records on crime and violence, and public expenditures data at the municipal level for Mexico (2005-2010), the analysis finds evidence indicating that drug-related crimes indeed deter growth. It also finds no evidence of a negative effect on growth from crimes unrelated to drug trafficking.